Proteomic Characterization of Zinc‐Binding Proteins of Canine Seminal Plasma. Issue 6 (20th October 2015) - Mogielnicka‐Brzozowska, M; Kowalska, N; Fraser, L; Kordan, W
Contents: The zinc‐binding proteins (ZnBPs) of the seminal plasma are implicated in different processes related to sperm–egg fusion. The aim of this study was to characterize the ZnBPs of canine seminal plasma using two‐dimensional polyacrylamide gel electrophoresis (2D‐PAGE) and mass spectrometry. The ZnBPs were isolated from the ejaculates of five dogs by affinity chromatography and subjected to 2D‐PAGE analysis. The acquired spots, detected across the gels, were analysed by mass spectrometry. Using 2D‐PAGE analysis, it was shown that canine seminal plasma comprised about 46–57 zinc‐binding polypeptides, with molecular mass ranging from 9.3 to 138.7 kDa and pI at pH 5.2–10.0. It was found that zinc‐binding polypeptides of low molecular masses (9.3–19.0 kDa and pI at pH 6.1–10.0) were predominant in the seminal plasma, and seven polypeptides, with molecular masses ranging from 11.7 to 15.4 kDa and pI at pH 6.8–8.7, were characterized by high optical density values. In addition, analysis with mass spectrometry (LC‐MS‐MS/MS) revealed that the identified seven polypeptides are canine prostate‐specific esterase (CPSE), which is the main proteolytic enzyme of the seminal plasma. The findings of this study indicate an important regulatory role of seminal plasma zinc ions in the functional activity of CPSE, which is of great significance for maintaining the normal function of canine prostate and the spermatozoa functions.